2017
DOI: 10.1038/sigtrans.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation in tumor cell epithelial–mesenchymal transition: molecular basis and therapeutic strategy

Abstract: Epithelial–mesenchymal transition (EMT) is recognized as a driving force of cancer cell metastasis and drug resistance, two leading causes of cancer recurrence and cancer-related death. It is, therefore, logical in cancer therapy to target the EMT switch to prevent such cancer metastasis and recurrence. Previous reports have indicated that growth factors (such as epidermal growth factor and fibroblast growth factor) and cytokines (such as the transforming growth factor beta (TGF-β) family) are major stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 176 publications
(187 reference statements)
1
138
0
Order By: Relevance
“…Additionally, ROS can induce metabolic reprogramming of cancer cells and surrounding stroma, facilitating tumor growth [61]; they are also able to act directly on EMTassociated pathways, driving the cancer phenotype [62]. Indeed, ROS accumulation may lead to increased cell mobility, diminished cell-cell conjunctions, cytoskeleton remodeling, downregulation of epithelial cell markers, upregulation of mesenchymal markers, and degradation of the extracellular matrix [63]. In agreement with this hypothesis, we demonstrated that the basal-like cell line MDA-MB-231 produces larger amounts of both extracellular and intracellular ROS compared to the MCF-7 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ROS can induce metabolic reprogramming of cancer cells and surrounding stroma, facilitating tumor growth [61]; they are also able to act directly on EMTassociated pathways, driving the cancer phenotype [62]. Indeed, ROS accumulation may lead to increased cell mobility, diminished cell-cell conjunctions, cytoskeleton remodeling, downregulation of epithelial cell markers, upregulation of mesenchymal markers, and degradation of the extracellular matrix [63]. In agreement with this hypothesis, we demonstrated that the basal-like cell line MDA-MB-231 produces larger amounts of both extracellular and intracellular ROS compared to the MCF-7 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] As such, modulation of ROS levels in cancer cells has been put forth as another promising strategy to tackle the problem of local invasiveness and metastization of cancer. 22 One possible strategy to modulate the levels of cellular ROS, and, consequently, the cancer cells metastatic ability, is the use of metal-based compounds that mimic the superoxide dismutase (SOD) and catalase (CAT) enzymes, important cellular antioxidant proteins that are responsible for maintaining the cellular redox balance. 22 For that purpose, in this work, we used two coordination compounds harboring the ligand 2-{[(3chloro-2-hydroxy-propyl)-pyridin-2-ylmethyl-amino]-methyl}phenol (L) complexed with iron (FeL) 23,24 and copper (CuL).…”
Section: Introductionmentioning
confidence: 99%
“…22 One possible strategy to modulate the levels of cellular ROS, and, consequently, the cancer cells metastatic ability, is the use of metal-based compounds that mimic the superoxide dismutase (SOD) and catalase (CAT) enzymes, important cellular antioxidant proteins that are responsible for maintaining the cellular redox balance. 22 For that purpose, in this work, we used two coordination compounds harboring the ligand 2-{[(3chloro-2-hydroxy-propyl)-pyridin-2-ylmethyl-amino]-methyl}phenol (L) complexed with iron (FeL) 23,24 and copper (CuL). 25 We thus describe for the rst time the application of these compounds in the frontier of chemistry and human oncology, by assessing their antioxidant and antimetastatic potential in glioma (H4) cells.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, miRNAs have been implicated for their functions to drive poor prognosis cancer subtypes by regulating the expression of genes actively involved in epithelial-mesenchymal transition (EMT), a process in which loss of epithelial hallmarks and acquisition of mesenchymal features can be observed in cancer cells, enabling them to metastasize to distant organs [22,23]. Furthermore, it is well accepted that transforming growth factor-β (TGFβ) is a robust EMT inducer both under physiological and pathological circumstances [24]. As it has been reported that the squamous subtype of PDAC is associated with TGFβ activation [17], we hereby focus on the key miRNAs as well as their targets to dissect their regulatory mechanism specifically in the squamous PDAC subtype based on in silico analysis of multi-omics data.…”
Section: Introductionmentioning
confidence: 99%